Can Social Media, Digital Literacy, and Resilience influence Interest in Digital Entrepreneurship? Study on Students University - Muhammad Argo Aliffirmansyah; Choirul Nikmah (Journal of Office Administration : Education and Practice, 2025)
The digital era requires young people to be able to adapt to technological developments and emerging business opportunities. This study aims to analyze the influence of social media, digital literacy, and resilience on the interest in digital entrepreneurship among students at Surabaya State University. The research method used an associative quantitative approach with a sample of 225 students selected through proportional stratified random sampling. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was performed using multiple linear regression. The results showed that social media had a significant negative effect on interest in digital entrepreneurship, digital literacy had a significant positive effect, and resilience has a significant negative effect. Simultaneously, the three variables have a significant effect with a coefficient of determination. The implications of this study emphasize the importance of digital literacy in increasing interest in digital entrepreneurship, as well as the need for productive use of social media and an understanding of the appropriate role of resilience in career decision-making.